Cannabis smoking and lung cancer risk: Pooled analysis in the International Lung Cancer Consortium. Issue 4 (30th June 2014) - Zhang, Li Rita; Morgenstern, Hal; Greenland, Sander; Chang, Shen‐Chih; Lazarus, Philip; Teare, M. Dawn; Woll, Penella J.; Orlow, Irene; Cox, Brian; on behalf of the Cannabis; Respiratory Disease Research Group of New Zealand; Brhane, Yonathan; et al.
<x xml:space="preserve">Abstract</x> To investigate the association between cannabis smoking and lung cancer risk, data on 2, 159 lung cancer cases and 2, 985 controls were pooled from 6 case‐control studies in the US, Canada, UK, and New Zealand within the International Lung Cancer Consortium. Study‐specific associations between cannabis smoking and lung cancer were estimated using unconditional logistic regression adjusting for sociodemographic factors, tobacco smoking status and pack‐years; odds‐ratio estimates were pooled using random effects models. Subgroup analyses were done for sex, histology and tobacco smoking status. The shapes of dose‐response associations were examined using restricted cubic spline regression. The overall pooled OR for habitual versus nonhabitual or never users was 0.96 (95% CI: 0.66–1.38). Compared to nonhabitual or never users, the summary OR was 0.88 (95%CI: 0.63–1.24) for individuals who smoked 1 or more joint‐equivalents of cannabis per day and 0.94 (95%CI: 0.67–1.32) for those consumed at least 10 joint‐years. For adenocarcinoma cases the ORs were 1.73 (95%CI: 0.75–4.00) and 1.74 (95%CI: 0.85–3.55), respectively. However, no association was found for the squamous cell carcinoma based on small numbers. Weak associations between cannabis smoking and lung cancer were observed in never tobacco smokers. Spline modeling indicated a weak positive monotonic association between cumulative cannabis use and lung cancer, but precision was low at high exposure levels. Results from our pooled analyses provide little evidence for an increased risk of lung cancer among habitual or long‐term cannabis smokers, although the possibility of potential adverse effect for heavy consumption cannot be excluded.